Kapitalisme Tubuh Perempuan: Sebuah Pendisiplinan Atau Industrialisasi - Zahid, A; Ayu, Nitia Agustini Kala; Ikayanti, Riza Laely (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2023)
The beauty of women's bodies in the context of today's media has transformed into an object of public consumerism that cannot be avoided. The body is no longer just a biological form but an exploration of itself. Meanwhile, the exploration and expansion of the body have a very subtle difference, because, in the end, the body becomes a passive object during the self-egoists active subject. The demand for an ideal body in public discourse impels women to modify their bodies. The discourse on women's bodies is not only in the form of powerlessness over their bodies, but also political tendencies and powers that regulate women as objects of sexuality, women's body discourse becomes the most essential thing in political interests. As a result, taking care of the body and appearance has now become a necessity for women due to the demands of social construction which have a major influence on the ideal standard of female beauty. The body of women who transforms into consumptive materialism is used as an attraction for industrialization in a change in symbolic capital. This contestation was formed in the arena of consumerism, capitalism, hedonism, and patriarchal culture which resulted in increasingly strong women's constructivism in the industrialized world which is always associated with the problem of the negative image of women's bodies and self.